Oltre il Muro: verso l’Università di Lipsia - Misiti, Domenico (Chimica nella Scuola, 2022)
A journey to the University of Leipzig for a scientific collaboration is an opportunity for the Author to report his feelings and sensations in the presence of the Berlin Wall.